Corona-Covid-19 virus and its impact on the use of electronic information sources : a field study to identify the extent to which students in the various educational stages use electronic sources of information to meet their cognitive and informational needs for distance learning in some countries... - تريزا وليم عزمى (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims to identify the extent of the impact of the spread of thecoronavirus Covid-19 on the use of electronic sources by beneficiaries at differenteducational stages to meet their knowledge and information needs for distancelearning in some countries of the world, namely Egypt- Qatar – USA . Where thestudy included many sections, the first of which included the theoretical section,which included the methodology of the study and consisted of the introduction -the importance of the study and the reasons for choosing the subject - studyquestions - study limits - study methodology / study and data collection tools -previous studies as well as the definition of the virus corona in general and Covid- 19 in particular and what sources of electronic information, and the stage of itsdevelopment over time and the most important physical forms within libraries andinformation centers that have become the most important information facilities inmodern times, Then the study moved to the practical aspect, which consisted inthe preparation of electronic questionnaire in Both Arabic and English so thatnon-Arabic speakers can answer it, in order to measure the impact of thecoronavirus on the use of electronic sources, where the questionnaire includedthe number of eleven different questions to cover all aspects of the study, andspecific so that the study community can answer it in order to achieve theprinciple of ease and speed where the number of sample study and whichresponded 554 students to be the basis of the statistical work and To reach theresults of the study .